Energy storage material prepared from seaweed hydrothermal liquefaction byproducts, method and electrode

By using the ash of the hydrothermal liquefied solid phase as a template and activator, combined with bio-oil for co-carbonization, high-performance biochar electrode materials were prepared, which solved the problems of environmental pollution and resource utilization efficiency in traditional technology, and achieved the Green and economical preparation of energy storage materials.

CN119263274APending Publication Date: 2025-01-07JIANGSU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411541019.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize the solid phase ash in the hydrothermal liquefaction by-product of seaweed, and traditional activators are environmentally destructive, limiting the preparation and application of biochar electrode materials.

Method used

The ash of the hydrothermal liquefied solid phase of seaweed is used as the self-source template agent and activator, and combined with liquefied bio-oil for co-carbonization, and the energy storage material biochar with good electrochemical properties is prepared, and mixed with binder and carbon black. Prepare electrodes to avoid the use of environmentally destructive chemicals.

Benefits of technology

It is realized that electrode materials with considerable electrochemical properties can be prepared without adding environmentally destructive reagents, which reduces the manufacturing cost of supercapacitors, improves market competitiveness, and achieves green and sustainable resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263274A_ABST
    Figure CN119263274A_ABST
Patent Text Reader

Abstract

The invention provides an energy storage material prepared from seaweed hydrothermal liquefaction byproducts, a method and an electrode, and the method comprises the following steps: treating seaweed into seaweed powder, carrying out hydrothermal liquefaction, and collecting a liquid-phase product and solid-phase residues to obtain a solid-liquid mixture; primarily separating a solid-liquid mixture by using a centrifugal machine, secondarily separating a liquid-phase product by using a filtering device, collecting an oil-phase product, and drying solid-phase residues for later use; and sufficiently and uniformly mixing the oil phase and the solid phase residues, drying, pyrolyzing, synthesizing a carbon material, sequentially pickling and washing the collected product, and drying to obtain the energy storage material charcoal. According to the method, SiO2 in the solid-phase residue ash is used as a self-source template agent, a metal compound is used as a self-source activating agent, the template-like and activating effects of a seaweed hydrothermal liquefied solid phase are utilized, an electrode material with considerable electrochemical performance is prepared under the condition that no chemical reagent with environmental destructiveness is added, the manufacturing cost of a supercapacitor is reduced, and the method is suitable for large-scale popularization and application. The preparation process is simple, and the technological process is green and energy-saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomass resource utilization, and in particular relates to an energy storage material, method and electrode prepared by utilizing seaweed hydrothermal liquefaction byproducts. Background Art

[0002] As a "zero-carbon" fuel, biomass has the advantages of being renewable, abundant, clean, and cost-effective. It is an ideal renewable carbon-neutral resource. Using biomass energy to replace fossil fuels to produce high-value chemicals is a current research hotspot. In addition, the energy and resource utilization of biomass waste can simultaneously solve environmental pollution problems, energy and resource shortages, and form a virtuous cycle of environmental protection and economic development, which has important environmental, economic and social benefits. Compared with other biomass, algae have the advantages of short growth cycle, high yield, small footprint, and strong CO2 fixation capacity. The thermochemical conversion technology of hydrothermal liquefaction (HTL) can directly use wet biomass as raw material to produce bio-crude oil. The bio-oil yield obtained is moderate (40-83%) and the calorific value is considerable (28-40MJ / kg). Although HTL technology has great development potential, few people pay attention to the high-value utilization of the solid byproduct (HC) obtained by hydrothermal liquefaction. HC exists in the form of biochar, which is usually used as an adsorbent after activation and modification, but this cannot give full play to the role of ash in the solid phase. Industrial analysis shows that seaweed has more ash than general woody biomass, and because it grows in a marine environment, seaweed ash contains more K and Na elements. The ash content in the solid phase (HSC) obtained by seaweed hydrothermal liquefaction is as high as 30% to 50%, mainly composed of metal compounds such as K, Ga, Na, Mg, Al, Fe and minerals such as SiO2. The oxides in HSC ash can be roughly divided into acidic oxides (SiO2, Al2O3, etc.) and alkaline oxides (K2O, Na2O, Fe2O3, MgO, GaO, etc.) according to different ionic potentials, while alkali metal salts mainly exist in the form of KCl and NaCl. Alkali metals and chlorides have a great influence on the ash melting point. The higher their content, the easier it is to accumulate ash and slag; at the same time, the alkaline oxides in the ash also have the function of self-fixing sulfur. Therefore, it is possible to consider the comprehensive utilization of HSC ash to further realize the value-added benefits of seaweed hydrothermal liquefaction byproducts.

[0003] Supercapacitors are highly efficient and stable new energy storage devices that are flexibly used in the field of energy conversion and storage. They are regarded as the most promising new green energy devices in this century. Electrode materials are the core of energy storage devices. The electrode materials prepared from biochar for supercapacitors have the advantages of being cheap, simple, stable and renewable. They are the key research and development direction for realizing the high-value and economical application of biochar. Biochar with rich pore structure and active sites is usually produced by chemical activation, template method or metal modification. The hierarchical porous structure of biochar can not only provide charge storage places, but also provide fast ion transmission channels, thereby realizing energy storage and conversion. Therefore, there is a lot of room for development in the application of biochar in supercapacitor electrode materials.

[0004] In recent years, a lot of research has been conducted on the preparation of biochar-based electrode materials from different biomass precursors. The original biomass precursor itself has a chemical bond cross-linked network, which is prone to structural shrinkage during the carbonization process, resulting in pore blockage, making it impossible for the internal space of the biochar to fully contact the activator to achieve pore formation. However, compared with traditional native biomass, bio-oil has stronger cross-linking polymerization characteristics and thermoplasticity, and the growth of the carbon skeleton during the carbonization process is not constrained by the native skeleton structure, which is easy to be infiltrated by templates and activators, and is a potential carbon source for the preparation of energy storage materials. In addition, traditional strong alkaline activators are highly corrosive and polluting, which can easily cause equipment damage, increase maintenance costs, and are not sustainable. Therefore, the development and utilization of green and renewable activators to replace traditional chemical reagents is one of the key issues in achieving green energy storage. Summary of the invention

[0005] In response to the above technical problems, the present invention provides a method for preparing energy storage materials using seaweed hydrothermal liquefaction by-products. The template-like and activation effects of the seaweed hydrothermal liquefaction solid phase are utilized to successfully prepare the energy storage material biochar without adding any environmentally destructive chemical reagents.

[0006] The present invention utilizes the ash in the solid phase byproduct of seaweed hydrothermal liquefaction as a self-source template and activator, and the rest of the byproduct and liquefied bio-oil are used as carbon sources for co-carbonization, and finally synthesizes an energy storage material with good electrochemical performance.

[0007] The present invention also provides an energy storage material prepared using seaweed hydrothermal liquefaction byproducts, and biochar prepared according to the method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts.

[0008] The present invention also provides an electrode, which is made by mixing the energy storage material biochar prepared using the by-product of seaweed hydrothermal liquefaction with a binder, carbon black and N-methylpyrrolidone to form a uniform slurry. The electrode prepared by the present invention has considerable electrochemical performance without adding any environmentally destructive chemical reagents.

[0009] The present invention is a method for synthesizing energy storage carbon materials by self-activating and controlling the shape of solid phase byproducts of seaweed hydrothermal liquefaction, including seaweed hydrothermal liquefaction and carbonization of solid phase residue and preparation of supercapacitor electrode materials. The present invention innovatively proposes to utilize the template-like and activation effects of the solid phase of seaweed hydrothermal liquefaction, and successfully prepares electrode materials with considerable electrochemical performance without adding any environmentally destructive chemical reagents. Specifically, the ash of the solid phase residue contains SiO2 and metal compounds; SiO2 has a unique crystal structure and excellent thermal stability, can maintain high strength and hardness at high temperatures, and can be used as a self-source template agent. K and Na alkali metals in the metal compound are easy to evaporate at high temperatures to form metal vapor, which can be used as a self-source activator. The present invention fully utilizes the carbon and various minerals fixed by the growth of seaweed through thermochemical conversion technology, thereby obtaining value-added energy storage products, which is of great significance to maintaining the ecological environment and realizing green energy storage.

[0010] The present invention achieves the above technical objectives through the following technical means.

[0011] The present invention is achieved through the following technical solutions:

[0012] A method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts comprises the following steps:

[0013] Step S1, processing seaweed into algae powder, performing hydrothermal liquefaction, collecting liquid products and solid residues, and obtaining a solid-liquid mixture;

[0014] Step S2, using a centrifuge to preliminarily separate the solid-liquid mixture, using a filtering device to secondary separate the liquid phase product, collecting the oil phase product, and drying the solid phase residue for later use;

[0015] Step S3, the oil phase and the solid phase residue are fully mixed and then dried for pyrolysis to synthesize carbon materials, and the collected products are acid-washed and water-washed in turn and then dried to obtain energy storage material biochar.

[0016] In the above scheme, the type of seaweed in step S1 is Enteromorpha fasciata, Sargassum fusiformis or Sargassum.

[0017] In the above scheme, the working conditions of the seaweed hydrothermal liquefaction in step S1 are specifically:

[0018] The seaweed is processed into seaweed powder with a fineness of 50 to 100 meshes, the temperature of hydrothermal liquefaction is 250 to 350°C, the time is 25 to 45 minutes, and the solid-liquid ratio of the seaweed powder to water is 1:5 or 1:10.

[0019] In the above scheme, the centrifuge in step S2 is preferably a low-speed centrifuge, the centrifugal speed of the low-speed centrifuge is 3000-5000r / min, the time is 10-15min, and dichloromethane is used to separate the water phase and the oil phase in the liquid phase product, and the oil phase is collected.

[0020] Preferably, the filtering device is a vacuum filtering device.

[0021] In the above scheme, the ash of the solid phase residue collected by the hydrothermal liquefaction of seaweed contains metal compounds and SiO2. The metal compounds serve as self-source metal activators for synthesizing carbon materials in step S3; SiO2 serves as self-source templates for synthesizing carbon materials in step S3.

[0022] The solid phase residue collected by the seaweed hydrothermal liquefaction has a high ash content (30-50%), which is mainly composed of inorganic salts and minerals, and contains metal compounds and SiO2. Among them, the rich metal compounds such as K and Na are easy to evaporate at high temperature to form metal vapor, which serves as a self-source metal activator for synthesizing carbon materials in step S3; SiO2 has a unique crystal structure and excellent thermal stability, and can maintain high strength and hardness at high temperatures, and serves as a self-source template for synthesizing carbon materials in step S3.

[0023] In the above scheme, the mixing mass ratio of the oil phase to the solid phase in step S3 is 1:2 to 1:5.

[0024] In the above scheme, the oil phase and the solid phase are mixed in step S3 as follows:

[0025] At room temperature, 10 to 20 mL of ethanol is added to the mixture and stirred on a magnetic stirrer for 30 to 60 min. The mixture is dried and crushed for later use. Preferably, the mixture is dried in an oven at 60 to 80°C.

[0026] In the above scheme, the reaction conditions for pyrolysis in step S3 are:

[0027] The pyrolysis temperature was set at 800°C, the heating rate was 5-10°C / s, the nitrogen flow rate was 50-100 mL / min, and the set temperature was maintained for 1-2 hours. After the reaction was completed, the mixture was cooled to room temperature and then taken out.

[0028] In the above scheme, the conditions for pickling and washing in step S3 are:

[0029] The pyrolysis product was placed in a mixture of 2M HCl and 10% HF and stirred continuously for 12 to 24 hours, then washed with deionized water until the solution was neutral, and the obtained biochar was collected and dried.

[0030] An energy storage material prepared by utilizing byproducts of seaweed hydrothermal liquefaction, and biochar prepared according to the method for preparing energy storage material by utilizing byproducts of seaweed hydrothermal liquefaction.

[0031] An electrode is made by mixing the energy storage material biochar prepared by utilizing the byproduct of seaweed hydrothermal liquefaction with a binder, carbon black and N-methylpyrrolidone to form a uniform slurry.

[0032] In the above scheme, the electrode is made of biochar, an energy storage material prepared by utilizing the byproduct of seaweed hydrothermal liquefaction, as an active material, carbon black as a conductive agent, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent, which is mixed into a uniform slurry, coated on nickel foam, dried, and pressed into sheets. The electrode is a seaweed carbon electrode.

[0033] Preferably, the method for making the electrode is specifically as follows: using the biochar prepared by the method for preparing energy storage materials using the byproducts of seaweed hydrothermal liquefaction as the active material, carbon black as the conductive agent, polyvinylidene fluoride as the binder, N-methylpyrrolidone as the solvent, biochar, carbon black, polyvinylidene fluoride are mixed into a slurry in a mass ratio of 8:1:1 and coated on the nickel foam, and placed in an oven at 80-100°C for 6-12 hours. The dried nickel foam is weighed and pressed into a sheet for electrochemical performance testing. The prepared carbon electrode is used as the working electrode, the platinum sheet is used as the counter electrode, and the mercury / mercury oxide electrode is used as the reference electrode to form a three-electrode system. The electrochemical test is performed in 6MKOH electrolyte using Shanghai Chenhua CHI 760E electrochemical workstation, including cyclic voltammetry (CV), constant current charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS).

[0034] The ash in the solid phase (HSC) obtained by hydrothermal liquefaction of seaweed of the present invention contains more SiO2, has a unique crystal structure and excellent thermal stability, is structurally stable at high temperatures, is not easy to decompose, and can be used as a template. During the carbonization process, the thermoplastic bio-oil penetrates the framework of the hard template to form a coating structure. At the same time, the carbon oxides (such as aldehydes, ketones, phenols and furans, etc.) in the bio-oil and HSC form carbonaceous materials through aldol condensation, cycloaddition or cross-linking polymerization. After the carbonization is completed, the template structure is removed by acid washing, and the carbon wall is easy to form macropores and mesopores, and even inherits a certain skeleton structure.

[0035] In addition, the ash of HSC contains more potassium and sodium than wood biomass. These alkali metals are easy to evaporate at high temperatures and have a certain activation etching effect. The evaporation of alkali metals includes two stages. The initial stage is the precipitation of organic sodium and organic potassium, and the high-temperature stage is the entry of inorganic sodium and inorganic potassium into the gas phase due to the increase in vapor pressure. The evaporation of alkali metals in seaweed ash is mainly the volatilization of KCl and NaCl vapor, which is a typical self-source activator. During the high-temperature carbonization process of this type of alkali metal with the carbon source, due to the evaporation of metal vapor, the carbon surface will be etched by steam to form micropores and partial mesopores, thereby realizing metal activation pore formation.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The outbreak of algae such as Enteromorpha will not only cause eutrophication of water bodies, but also cause damage to aquatic products, destruction of ecological balance and other disadvantages that are not conducive to natural and economic development. Therefore, the resource utilization of algae wet biomass is of great significance. Seaweed hydrothermal liquefaction realizes the energy utilization of algae through thermal decomposition. The bio-crude oil produced can be used as a green fuel to replace fossil energy, and the remaining solid byproducts accumulate metals and minerals absorbed by algae growth, which are potential activators and templates for synthetic energy storage materials. The SiO2 in the solid phase residue ash of the present invention is used as a self-source template agent, and the metal compound is used as a self-source activator. It is innovatively proposed to utilize the template-like and activation effect of the solid phase of seaweed hydrothermal liquefaction, and successfully prepare electrode materials with considerable electrochemical performance without adding any environmentally destructive chemical reagents. The present invention reduces the manufacturing cost of supercapacitors and improves their market competitiveness. Different from the traditional scheme for preparing activated carbon, the material preparation process is simple, avoiding cumbersome and energy-consuming steps such as pre-carbonization, pre-baking and addition of exogenous N, and the process flow is green and energy-saving. The system's raw materials are green and renewable, with high overall utilization and low energy consumption, and it has high cost benefits and environmental value.

[0038] Note that the description of these effects does not prevent the existence of other effects. One embodiment of the present invention does not necessarily have all of the above effects. Effects other than the above can be clearly seen and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the constant current charge and discharge curve of Example 2 and Example 3 of the present invention at a current density of 0.5A / g.

[0040] Figure 2 The cyclic voltammetry curves of Example 2 and Example 3 of the present invention at a scan rate of 10 mV / s.

[0041] Figure 3 3 are the Nyquist curves of Example 2 and Example 3 of the present invention.

[0042] Figure 4 : is the SEM picture of Example 2 and Example 3 of the present invention, wherein Figure 4 (a) is a SEM image of the carbon material SC prepared from the solid phase byproduct obtained by hydrothermal liquefaction of seaweed. Figure 4 (b) is a SEM image of the carbon material OC prepared from bio-oil obtained by hydrothermal liquefaction of seaweed. Figure 4 (c) is the SEM image of the carbon material O1S4C prepared by mixing bio-oil obtained from hydrothermal liquefaction of seaweed and solid by-products.

[0043] Figure 5 2 is a nitrogen adsorption / desorption curve diagram of Examples 2 and 3 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto. The reagents, materials, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0045] Example 1

[0046] In this embodiment 1, the type of seaweed is Enteromorpha fascicularis. A method for preparing energy storage materials using the byproducts of seaweed hydrothermal liquefaction comprises the following steps:

[0047] Enteromorpha was processed into algae powder with a fineness of 50 mesh for hydrothermal liquefaction. The specific working conditions were: temperature of 250℃, time of 25min, and solid-liquid ratio of algae powder to water of 1:5. The solid-liquid mixture obtained by hydrothermal liquefaction was separated using a low-speed centrifuge (centrifugal speed of 3000r / min, time of 10min), and the oil phase was further separated and collected using 50mL of dichloromethane, and the solid residue was placed in an oven to dry for 24h. At room temperature, 0.5g of oil and 1.5g of solid phase were placed in a beaker and 10mL of ethanol was added. The mixture was continuously stirred on a magnetic stirrer for 30min, and the mixture was placed in a 60℃ oven for drying, crushed and set aside. The crushed particles were placed in a quartz dish for pyrolysis, the pyrolysis temperature was set to 800℃, the heating rate was 5℃ / s, the nitrogen flow rate was 60mL / min, and the set temperature was maintained for 1.5h. After the reaction was completed, the mixture was cooled to room temperature and taken out. The pyrolysis product was placed in a mixture of 2M HCl and 10% HF and stirred for 12 h. It was then washed with deionized water until the solution was neutral. The resulting biochar was collected and dried in an oven at 100°C for 12 h.

[0048] The method for preparing an electrode by using the biochar energy storage material prepared by using the byproduct of seaweed hydrothermal liquefaction as an active material, carbon black as a conductive agent, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent to mix into a slurry and coat it on nickel foam, specifically comprising the following steps:

[0049] Weigh 8 mg of the above biochar, 1 mg of carbon black and 1 mg of polyvinylidene fluoride, add 2 ml of N-methylpyrrolidone, mix into a uniform slurry and coat it on the nickel foam, and place it in an oven at 80°C to dry for 10 hours. The dried nickel foam was weighed and pressed into sheets for electrochemical performance testing. The prepared carbon electrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the mercury / mercury oxide electrode was used as the reference electrode to form a three-electrode system. The electrochemical test was carried out using the Shanghai Chenhua CHI 760E electrochemical workstation in 6M KOH electrolyte, and the specific capacitance range was measured to be 180-200F / g at a current density of 0.5A / g.

[0050] Example 2

[0051] In this embodiment 2, the type of seaweed is Sargassum fusiformis. A method for preparing an energy storage material using a byproduct of hydrothermal liquefaction of seaweed includes the following steps:

[0052] The algae powder with a fineness of 100 mesh was processed by hydrothermal liquefaction. The specific working conditions were: temperature of 320℃, time of 30min, and solid-liquid ratio of algae powder to water of 1:10. The solid-liquid mixture obtained by hydrothermal liquefaction was separated by a low-speed centrifuge (centrifugal speed of 5000r / min, time of 15min), and the oil phase was further separated and collected by 50mL of dichloromethane, and the solid residue was placed in an oven to dry for 12h. At room temperature, 0.5g of oil and 2g of solid phase were placed in a beaker and 15mL of ethanol was added. The mixture was continuously stirred on a magnetic stirrer for 45min, and the mixture was placed in an oven at 80℃ for drying, crushed and set aside. The crushed particles were placed in a quartz dish for pyrolysis, the pyrolysis temperature was set to 800℃, the heating rate was 10℃ / s, the nitrogen flow rate was 80mL / min, and the set temperature was maintained for 2h. After the reaction was completed, the mixture was cooled to room temperature and taken out. The pyrolysis product was placed in a mixture of 2M HCl and 10% HF and stirred for 12 h. It was then washed with deionized water until the solution was neutral. The resulting biochar was collected and dried in an oven at 80 °C for 24 h.

[0053] The method for preparing an electrode by using the biochar energy storage material prepared by using the byproduct of seaweed hydrothermal liquefaction as an active material, carbon black as a conductive agent, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent to mix into a slurry and coat it on nickel foam, specifically comprising the following steps:

[0054] Weigh 8 mg of the above biochar, 1 mg of carbon black and 1 mg of polyvinylidene fluoride, add 2 ml of N-methylpyrrolidone, mix into a uniform slurry and coat it on the nickel foam, and place it in an oven at 85°C to dry for 8 hours. The dried nickel foam was weighed and pressed into sheets for electrochemical performance testing. The prepared carbon electrode O1S4C was used as the working electrode, the platinum sheet was used as the counter electrode, and the mercury / mercury oxide electrode was used as the reference electrode to form a three-electrode system. The electrochemical test was carried out using Shanghai Chenhua CHI 760E electrochemical workstation in 6M KOH electrolyte.

[0055] The specific capacitance of O1S4C at a current density of 0.5A / g was measured to be in the range of 200 to 230F / g. Figure 1 As shown in the figure, the constant current charge-discharge curve of O1S4C at a current density of 0.5A / g is an approximately symmetrical triangle and has the longest charge-discharge time, indicating that its capacitance performance is better. Figure 2 As shown in the figure, the coil area enclosed by the cyclic voltammetry curve of O1S4C at a scan rate of 10mV / s is the largest, indicating that it has better electrochemical performance. Figure 3 As shown in the figure, the Nyquist curve of O1S4C has a smaller semicircle in the high frequency region, indicating that its charge transfer resistance is small, and the straight line in the low frequency region is closer to the vertical line, indicating that it has an ideal capacitance behavior. Figure 4 (b) and Figure 4 As shown in (c), O1S4C presents a more compact structure than OC. Figure 5 The nitrogen adsorption-desorption test shows that it has a richer pore structure.

[0056] Example 3

[0057] The algae powder with a fineness of 100 mesh was processed into hydrothermal liquefaction. The specific working conditions were: temperature of 320 ° C, time of 30 min, and solid-liquid ratio of algae powder to water of 1:10. The solid-liquid mixture obtained by hydrothermal liquefaction was separated using a low-speed centrifuge (centrifugal speed of 5000r / min, time of 15min), and the oil phase was further separated and collected using 50mL of dichloromethane, and the solid residue was placed in an oven to dry for 12h. 0.5g of oil and 2g of solid phase were taken respectively and placed in different quartz dishes for pyrolysis. The pyrolysis temperature was set to 800 ° C, the heating rate was 10 ° C / s, and the nitrogen flow rate was 80mL / min. After reaching the set temperature, it was maintained for 2h. After the reaction was completed, the product was cooled to room temperature and taken out. The solid phase pyrolysis product was placed in a mixture of 2M HCl and 10% HF and stirred for 12h, then washed with deionized water until the solution was neutral, and the obtained biochar was collected and dried in an oven at 80 ° C for 24h. The oil phase pyrolysis product does not contain ash and does not require acid washing and water washing.

[0058] The steps for preparing electrodes in this embodiment are the same as those in Example 2. A carbon electrode is prepared using the biochar as the active material and the electrochemical performance is tested. The carbon material OC prepared using bio-oil has a specific capacitance range of 45 to 60 F / g at a current density of 0.5 A / g, and the carbon material SC prepared using solid by-products has a specific capacitance range of 90 to 120 F / g at a current density of 0.5 A / g. Figure 1 Constant current charge and discharge test and Figure 2 Cyclic voltammetry test and Figure 3 The Nyquist curve results all show that OC has the worst electrochemical performance, followed by SC, and O1S4C has the best performance, which indicates that adding solid phase residue to bio-oil can effectively improve the energy storage properties of the material. Figure 4 As shown, it can be seen that SC shows a disordered hierarchical structure and has a certain aggregation tendency, such as Figure 4 (a) shows that the surface structure of OC is loose, such as Figure 4 (b) shows that the surface structure of O1S4C is compact and has an obvious aggregation tendency, such as Figure 4 As shown in (c), this is mainly caused by the template shaping of SiO2 in the solid phase byproduct. Figure 5 The nitrogen adsorption-desorption curve results also show that the addition of solid by-products to the oil phase enriches the pore structure of biochar, which is mainly caused by the activation and etching of alkali metals and the removal of template structure.

[0059] It should be understood that although this specification is described according to various embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

[0060] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts, characterized in that: The steps include: Step S1, processing seaweed into algae powder, performing hydrothermal liquefaction, collecting liquid products and solid residues, and obtaining a solid-liquid mixture; Step S2, using a centrifuge to preliminarily separate the solid-liquid mixture, using a filtering device to secondary separate the liquid phase product, collecting the oil phase product, and drying the solid phase residue for later use; Step S3, the oil phase and the solid phase residue are fully mixed and then dried for pyrolysis to synthesize carbon materials, and the collected products are acid-washed and water-washed in turn and then dried to obtain energy storage material biochar.

2. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: The type of seaweed in step S1 is Enteromorpha fasciata, Sargassum fusiformis or Sargassum.

3. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: The specific working conditions of the seaweed hydrothermal liquefaction in step S1 are: The seaweed is processed into seaweed powder with a fineness of 50 to 100 meshes, the temperature of hydrothermal liquefaction is 250 to 350°C, the time is 25 to 45 minutes, and the solid-liquid ratio of the seaweed powder to water is 1:5 or 1:

10.

4. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: In step S2, the centrifugal speed of the low-speed centrifuge is 3000-5000 r / min for 10-15 min, and dichloromethane is used to separate the water phase and the oil phase in the liquid phase product, and the oil phase is collected.

5. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: The ash of the solid phase residue collected by the seaweed hydrothermal liquefaction contains metal compounds and SiO2. The metal compounds serve as a self-source metal activator for synthesizing carbon materials in step S3; SiO2 serves as a self-source template for synthesizing carbon materials in step S3.

6. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: In step S3, the mixing mass ratio of the oil phase to the solid phase is 1:2 to 1:5; The oil phase and the solid phase are mixed in the following manner: at room temperature, 10 to 20 mL of ethanol is added to the mixture and the mixture is continuously stirred on a magnetic stirrer for 30 to 60 minutes, the mixture is dried, crushed and set aside.

7. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: The reaction conditions for pyrolysis in step S3 are: The pyrolysis temperature was set at 800°C, the heating rate was 5-10°C / s, the nitrogen flow rate was 50-100 mL / min, and the set temperature was maintained for 1-2 hours. After the reaction was completed, the mixture was cooled to room temperature and then taken out.

8. The method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to claim 1, characterized in that: The conditions for pickling and washing in step S3 are: The pyrolysis product was placed in a mixture of 2M HCl and 10% HF and stirred continuously for 12 to 24 hours, then washed with deionized water until the solution was neutral, and the obtained biochar was collected and dried.

9. An energy storage material prepared using seaweed hydrothermal liquefaction byproducts, characterized in that: Biochar prepared by the method for preparing energy storage materials using seaweed hydrothermal liquefaction byproducts according to any one of claims 1-8.

10. An electrode, characterized in that: The biochar is prepared by mixing the energy storage material biochar prepared by utilizing the byproduct of seaweed hydrothermal liquefaction as claimed in claim 9 with a binder, carbon black and N-methylpyrrolidone to form a uniform slurry.

Citation Information

Cited By

  • High-adsorption-performance environment-friendly seaweed carbon material and preparation method thereof

    CN121571108A